L4/5 and L5/S1 disc protrusions: analysis of 323 cases operated on over 12 years. Issue 9 (September 1979) - Shannon, N; Paul, E A
Abstract : A retrospective study of the results of excision of L4/5 and L5/S1 intervertebral discs in 323 patients operated on between January 1965 and January 1977 was undertaken. In every case the amount of disc excised was weighed immediately after operation. The patients had been followed up at the hospital for periods of between one and 14 years. As assessment was made of the clinical state of each patient at the end of follow-up. There was no evidence that the weight of disc excised affected the prognosis with respect either to the clinical state of the patient at the end of follow-up, or to the probability of recurrence of disc protrusion.